Evaluating the ecological state of Chinese Lake Baiyangdian (BYD) based on Ecological Network Analysis. (August 2021) - Zeng, Yong; Zhao, Yanwei; Qi, Zefeng
Highlights: A general integrated evaluation framework is proposed to assess ecological state of freshwater lakes or reservoirs. Lake Baiyangdian (BYD)'s ecosystem is divided into 15 functional groups. Ecological state of Lake BYD is quantified based on the performance of its structure and function. It is concluded that ecological state of Lake BYD in 2009–2010 could be graded "Bad". Abstract: Understanding the structure and function of a lake's ecosystem is the premise and foundation to implementing ecosystem-based management. However, evaluating the status of the ecosystem of a lake as a whole is still difficult when it comes to selecting indicators, determining standards, and interpretating results. In order to quantify the ecosystem status of Lake Baiyangdian (BYD), a holistic food web model was built using Ecopath with Ecosim. Eleven Ecological Network Analysis indicators classified into three categories (ecological function, ecological maturity, and food web structure) were selected according to their representativeness and availability. Based on the published literature on similar freshwater lakes or reservoirs in the world, quantile-based classification criteria are obtained. Furthermore, the Analytic Hierarchy Process was employed to assign the weight of an indicator according to its importance, sensitivity, and adaptability. An integrated evaluation framework was formed after synthesizing the evaluation value using a fuzzy comprehensive evaluation method. It was concluded that the ecological state of Lake BYD in 2009–2010 could be graded "Bad", featuring a low-quality mature ecosystem, low trophic transfer efficiency, and linear, simple, and fragile connections between trophic levels. More specifically, the "Medium" grade detritivory:herbivory ratio (D:H), mean trophic level of the catch (MTLC), and "Bad" grade of transfer efficiency (TE) indicate that the composition of trophic species is unbalanced and the material and energy transfer is inefficient. "Good" grades of total primary production over biomass (TPP/TB), biomass over total system throughput ratio (TB/TST), and relative ascendency (A/C), together with "Median" grade of total primary production over total respiration ratio (TPP/TR), show characteristics of a mature ecosystem due to a high biomass of macrophytes, although here is a "low quality" in terms of exergy. In terms of the performance of the food web structure, all indicators achieve a "Bad" grade, suggesting a linear, simple, and fragile network. According to our modeling results, controlling the excessive macrophyte biomass, restoring fish biodiversity, and mitigating the pressures of overexploitation are suggested for the ecosystem-based management of BYD. This paper provides an integrated method to evaluate the ecological state of a shallow lake when its own reference state is unavailable.